Modulating crystal grain size and optoelectronic properties of perovskite films for solar cells by reaction temperature. Issue 6 (27th January 2016) - Ren, Xiaodong; Yang, Zhou; Yang, Dong; Zhang, Xu; Cui, Dong; Liu, Yucheng; Wei, Qingbo; Fan, Haibo; Liu, Shengzhong (Frank)
Abstract : By regulating the reaction temperature during the direction contact and intercalation process (DCIP) for the transition from PbI2 to CH3 NH3 PbI3, both the crystal size and the electrical properties of the film have been modulated. Abstract : Regulating the temperature during the direction contact and intercalation process (DCIP) for the transition from PbI2 to CH3 NH3 PbI3 modulated the crystallinity, crystal grain size and crystal grain orientation of the perovskite films. Higher temperatures produced perovskite films with better crystallinity, larger grain size, and better photovoltaic performance. The best cell, which had a PCE of 12.9%, was obtained on a film prepared at 200 °C. Further open circuit voltage decay and film resistance characterization revealed that the larger grain size contributed to longer carrier lifetime and smaller carrier transport resistance, both of which are beneficial for solar cell devices.